Judith Trachtenberg: A Novel - Franzos, Karl Emil, 1848-1904; Lewis, Charlton Thomas, 1834-1904; Lewis, L. P. (Salt Lake City, UT : Project Gutenberg, 2011)
"Judith Trachtenberg: A Novel" by Karl Emil Franzos is a historical novel written in the late 19th century. The story revolves around Nathaniel Trachtenberg, a successful Jewish chandler in Eastern Galicia, and his two children, Raphael and Judith, who navigate the complexities of identity, love, and societal expectations in a divided community. The narrative explores themes of cultural heritage, the struggle for acceptance, and the tensions between tradition and modernity. At the start of the book, we are introduced to Nathaniel Trachtenberg, who prides himself on balancing his success with his adherence to Jewish customs, while his children grapple with their identities among both Jewish and Christian peers. Raphael, resentful of his Jewish background, distances himself from the Christian social circles, while Judith becomes increasingly entangled in them due to her beauty and charm. Their contrasts create familial tension, especially as their father contemplates arranged marriages for his children. This complex dynamic is sharply intensified following an incident at a ball where Judith's interactions with Christian suitors draw scrutiny, culminating in emotional conflicts that lay the groundwork for the story's exploration of love and cultural divides. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Judith_Trachtenberg
Release date is 2011-08-01
Produced by Charles Bowen, from page scans provided by the Web Archive
Keywords: Man-woman relationships -- Fiction; Poland -- Fiction; Jews -- Fiction